Warriors of the Amazon a Nova production by CSL Films for WGBH in association with channel 4. - Lizot, Jacques; Curling, Chris; Jillings, Andy (WGBH Video, 1996)
Visit the Yamomamo Indians, an endangered tribe whose culture is built on communal harmony and fierce rivalries.